Characterization and Monitoring of the Furggwanghorn Rock Glacier, Turtmann Valley, Switzerland: Results from 2010 to 2012. Issue 1 (4th February 2013) - Buchli, Thomas; Merz, Kaspar; Zhou, Xiaohai; Kinzelbach, Wolfgang; Springman, Sarah M.
Abstract : Climate effects relating to air temperature, radiation, snow cover, and rainfall combine with thaw and infiltration processes to cause changes in the thermal response and associated creep deformations in rock glaciers, which are the geomorphological expression of Alpine permafrost. The annual surface creep of some rock glaciers has accelerated recently by an order of magnitude. A multidisciplinary field study links characterization, monitoring, and modeling for such a rock glacier in the Turtmann valley in Switzerland. The first phase consisted of characterization using seismic refraction and ground‐penetrating radar (GPR), as well as borehole information and monitoring of meteorological, hydrothermal, and geotechnical variables over 2 yr. The ground model confirmed the heterogeneity of the internal structure, with rock glacier topography affecting the thermal distribution in boreholes and seepage flows from tracer tests at between 10 and 40 m h −1 . Temperatures were generally warmer than −0.25°C in the permafrost zone, with some variability in terms of thermal degradation of some layers to 0°C and an active layer of about 3 to 5 m depth. Unique internal shear movements were measured by an automatic inclinometer, which indicated downslope creep rates in the shear zone and at the surface of about 2.4 and 3.2 m yr −1 respectively, which could not be directly linked to temperature at the same depth. These rock glaciers have potential for future instability, which could damage infrastructure in the valley below. It is essential to understand why they have accelerated over the past decade through the complex interactions that have controlled the thermo‐hydromechanical response.